New Conceptual Design Of Portable Bamboo Bridge For Emergency Purposes - Musthaffa, Azrul Affandhi; Mohamad Nor, Norazman; Yusof, Mohammed Alias; Yaakob, Mohd Yuhazri (AIP Publishing, 2018)
Portable bridges serve as routes for troops during the military operations and the disaster relief operation. Nowadays, bamboo has been regarded as one of the alternative construction materials for building and bridge structures. This paper presents the conceptual design of the portable bridge. Several types of portable bridges and bamboo bridges are reviewed in the current work. The characteristics, capability and method of construction of each bridge are discussed. Finally, the conceptual of the portable bamboo bridge for emergency purposes is presented. The idea of producing portable bridge is proposed in the current work as it is crucial for providing route for communities affected by natural disasters.